Adverse Reactions to Vaccines: An Allergist's Approach (Actualité en allergologie et en immunologie au Canada, 2023)
Vaccination is one of the most impactful and cost-effective interventions for improving global health. Routine immunization has reduced mortality and morbidity resulting from numerous types of infectious diseases.The widespread use of any reagent is always associated with the risk of adverse reactions, including expected and common side effects, as well as those that are unexpected or idiosyncratic. Mild, local injection site reactions such as redness, tenderness, swelling, or constitutional symptoms such as fever and malaise, are common after vaccination and are not contraindications to further vaccination; they are generally manifestations of the physiologic response to vaccination. Uncommon reactions can vary; they may manifest as delayed hypersensitivity to vaccine components causing injection site nodules or severe, rare anaphylactic reactions. Anaphylaxis occurs at approximately one per million doses administered. The extremely rare Arthus reaction, a type of local Type 3 hypersensitivity reaction, resulting in local immune complex deposition due to the presence of pre-existing IgG antibodies, is typically limited in duration and is not a contraindication to further tetanus vaccination.Allergists are often seen as stewards of information regarding many of these reactions, although most of these reactions are not allergic in nature. It can be difficult to distinguish between a true allergic reaction to a vaccine and other clinical manifestations that may occur during or acutely after vaccination, such as anxiety, vasovagal responses, and pronounced local reactions. Patients who have had adverse reactions to vaccines may be unnecessarily advised to avoid subsequent immunization, which can put them at risk of morbidity or mortality. The importance of making this clinical distinction has become particularly significant during the ongoing COVID-19 pandemic. The allergist plays an important role in investigating adverse reactions to vaccines and ensuring that patients who are eligible can be safely vaccinated following appropriate investigation. For those patients with true immediate-onset allergic reactions, allergists are able to provide safe revaccination following established protocols.